Mutant androgen receptor detected in an advanced-stage prostatic carcinoma is activated by adrenal androgens and progesterone. - Zoran Čulig; Alfred Hobisch; Marcus V. Cronauer; Andrew C.B. Cato; A Hittmair; Christian Radmayr; Julia Eberle; G. Bartsch; Helmut Klocker (1993)
Structural changes of the androgen receptor (AR) may contribute to the development of resistance to endocrine therapy in prostatic carcinoma. We have isolated AR cDNA fragments from seven tumor specimens derived from patients with advanced metastatic prostatic tumors. In one specimen obtained from a patient who failed to respond to endocrine and cytotoxic therapy we have detected a point mutation in the hormone-binding domain of the receptor. This AR mutation is a guanine-to-adenine transition at nucleotide 2671 that leads to substitution of methionine for the wild type valine at position 715. It is a somatic mutation because it was not present in the AR genomic DNA fragments isolated from prostatic and testicular tissues of the same patient. The mutant AR was recreated in an expression vector and transiently expressed in COS-7 and CV-1 cells. Hormone-binding assays revealed that the mutant receptor does not differ from the wild type receptor in its ability to bind androgen. The dissociation constant for the synthetic androgen mibolerone was 3 nM for both receptors. There was also no significant difference in binding of other steroids and nonsteroidal antiandrogens as revealed by competition binding assays. However, transfection experiments to determine the trans-activation potential of the mutant receptor produced differences in the action of this receptor compared to the wild type receptor. Dihydrotestosterone and the synthetic androgens methyltrienolone (R1881) and mibolerone were equally proficient in conferring trans-activation activity to both the mutant and wild type receptors. Adrenal androgens such as dehydroepiandrosterone and androstenedione, as well as progesterone mediated a higher trans-activation through the mutant than through the wild type receptor. These data demonstrate that the exchange of a single valine into methionine at position 715 in the AR promoters trans-activation not only by testicular but also by adrenal androgens and progesterone. This pattern of ligand-dependent trans-activation may have significance in the process controlling the progression of prostatic carcinoma.